(untitled) (Journal of Oriental Studies, 2016)
This article analyzes the development and establishment of dramatic art in the second half of the twentieth century, namely in 50-80s of last century. This period is characterized by numerous dramatic works, which were included in the “golden fund” of the Egyptian literature.